Therapy, diagnosis and prognosis of chronic Chagas disease : insight gained in Argentina - Sosa-Estani, Sergio (2009)
Fil: Sosa-Estani, Sergio. ANLIS Dr.C.G.Malbrán. Centro Nacional de Diagnóstico e Investigación en Endemo-Epidemias; Argentina.